EVALUATION OF YIELD PERFORMANCE, ADAPTABILITY, AND DOWNY MILDEW RESISTANCE OF HYBRID MAIZE CANDIDATE BAY233 ACROSS DIVERSE ENVIRONMENT IN INDONESIA - Eko Budi Andriyanto; Muhammad Azrai (UIN Sunan Gunung Djati Bandung, 2026)
The development of high-yielding and well-adapted maize hybrids is essential for ensuring the sustainability of maize production in Indonesia. This study aimed to evaluate yield performance, adaptability, stability and downy mildew resistance of the hybrid candidate BAY233 across different agroecological environments. Multilocation trials were conducted during 2023-2024 planting season at ten testing locations representing major maize-production regions in Indonesia. The experiment was arranged in a randomized complete block design with six replications. BAY233 evaluated alongside with BAY234 and two commercial check varieties, BISI959 and NK7328. Yield performance was analyzed using analysis of variance (ANOVA), while genotype x environment (GxE) interaction and stability were assessed using the Additive Main Effects and Multiplicative Interaction (AMMI) model. Resistance to downy mildew was evaluated through artificial inoculation using Peronosclerospora philippinensis and P. maydis. BAY233 produced grain yields ranging from 8.43 to 12.40 t ha⁻¹ across test locations. Although its stability was slightly lower than that of BAY234 but still categorized as promising hybrid due to its performance. BAY233 demonstrated superior yield performance and broad adaptability. Furthermore, BAY233 exhibited strong resistance to downy mildew, as indicated by its low incidence under artificial inoculation test. These findings suggest that BAY233 is a promising hybrid candidate for commercial release and cultivation in Indonesia owning to its high yield potential, broad adaptability, and disease resistance.